Advanced accounting : a procedural approach vol. 2 - Guerrero, Pedro P.; Peralta, Jose F. (Manila, Philippines : GIC Enterprises & Co. Inc., 2013)
The emphasis throughout the book is on financial accounting concepts and on the application of these concepts to problems arising in both business and non-profit organizations.
CHAPTER 11. Home Office and branch Accounting - General procedures -- 12. Home Office and branch Accounting - Special Problems -- 13. Business Combinations -- 14. Consolidated Balance Sheet - Date of Acquisition -- 15. Consolidated Financial Statements - Subsequent to date of purchase-type business combination -- 16. Intercompany Profit transactions- Inventories -- 17. Intercompany Gain Transactions - Plant Assets -- 18. Accounting for foreign currency transactions -- 19. Translation of foreign currency Financial statements -- 20. Government Accounting system for National Government Agencies -- 21. Nonprofit Organizations.
Keywords: ACCOUNTING